P–235 Are morphokinetics parameters and profitability of an assisted reproduction cycle related to sperm selection technique? Microfluidic sperm sorter chip versus magnetic activated cell sorting. (6th August 2021) - Agud. Garcillan, D; Santamarí. López, E; Gonzále. Ravina, C; Pachec. Castro, A; Cru. Palomino, M; Requen. Miranda, A
Abstract: Study question: Does microfluidic sperm sorter offer any biological improvement over magnetic activated cell sorting (MACS)? Summary answer: Microfluidic approach for selecting high profile spermatozoa is as good as magnetic activated cell sorting in terms of morphokinetic, fertilization and good quality blastocyst rate. What is known already: Microfluidic sperm sorter chip is a method for select non-fragmented DNA sperm. We know that the use of these non-fragmented DNA sperms can improve the clinical results and the useful blastocyst rate. As several studies have shown previously, embryos morphokinetics parameters are affected by culture medium, ovarian stimulation, oxygen tension, origin of the oocytes, or the age of the patient, this is why we wanted to compare if the cleavage times using time lapse technology, are different depending on the sperm selection method used to select sperm with the non-fragmented DNA. Study design, size, duration: Prospective and observational study performed between May 2019 to January 2021 in IVI Madrid and IVI Sevilla. Seminal samples from couples participating in the study were divided into two aliquots; each of them was processed according to one of the study methods. 53 couples were included in the study. Half of the oocyte from each donor were microinjected with sperm selected through MACS (n = 281) and the other half through a microfluidic device (n = 275). Participants/materials, setting, methods: These oocytes were microinjected with both types of sperm samples and incubated in EmbryoScope. Cellular events studied in this study included cellular divisions until blastocyst stage, appearance and fading of some cellular structures and the duration of the first, second and third cellular cycle (cc1, cc2 and cc3) as well as their synchrony (S1, S2, S3). Data were exported from the EmbryoViewer data base. We perform an ANOVA statistical analysis to analyze the data. Main results and the role of chance: No significant differences between both sperm selection methods were found regarding the time of cell division (from T2 to Tblstocyst), the cellular cycles duration (cc1, cc2 and cc3) or the synchrony of the cellular cycles divisions (s1, s2 and s3). However, a clear trend towards statistical significance has been found in both duration of cc2 (p = 0.052) being longer in MACS embryos than in microfluidic sperm sorting embryos, and in the expansion of the blastocyst, which occurs earlier in embryos that come from MACS than in those that come from microfluidic sperm sorting (p = 0.097). These two events could indicate a better embryo cleavage dynamic in the case of MACS embryos, with a better blastocyst expandability and the necessary time to carry out all the biological events that must occur in the cc2. However, significant difference was found in the direct cleavage from 1 to 3 cells embryo stage, which is one of the adverse events that more affects embryo implantation, being higher in microfluidic sperm sorting group (p = 0, 037). Finally, the fertilization rate (73.1% vs 76.9%) and the good quality blastocyst rate (53.7% vs 56.5%) were higher in MACS embryos than in microfluidic sperm sorting embryos, although no significant differences were found. Limitations, reasons for caution: This study has been performed in donated oocytes, so these results may not be extrapolated to other groups of assisted reproduction patients. However, more data are needed to draw firm conclusions. Furthermore, it´s crucial to increase the sample size to check if the trends founded reach statistical significance. Wider implications of the findings: Microfluidic sorting of unprocessed semen in un unselected population is as efficacious as magnetic activated cell sorting according embryo morphokinetic, fertilization rate and useful blastocyst rate. Microfluidic sperm sorting does not show clinical advantage over MACS considering this data collection. Trial registration number: NCT04061484